Differential Gene Expression in the Otic Capsule and the Middle Ear—An Annotation of Bone-Related Signaling Genes. Issue 4 (April 2015) - Nielsen, Michelle C.; Martin-Bertelsen, Tomas; Friis, Morten; Winther, Ole; Friis-Hansen, Lennart; Rye-Jørgensen, Niklas; Bloch, Sune; Sørensen, Mads S.
<x xml:space="preserve">Abstract</x> Hypothesis A number of bone-related genes may be responsible for the unique suppression of perilabyrinthine bone remodeling. Background Bone remodeling is highly inhibited around the inner ear space most likely because of osteoprotegerin (OPG), which is a well-known potent inhibitor of osteoclast formation and function. However, other signaling molecules may also be responsible for the inhibition of bone remodeling within the otic capsule. Methods Microarray technology was used to determine bone-related genes differentially expressed between the lining tissues of the otic capsule (spiral ligament and stria vascularis) and the lining tissues from the middle ear of the rat. Data was analyzed with statistical bioinformatics tools. Gene expression levels of selected genes were validated using quantitative polymerase chain reaction. Results A total of 413 genes were identified when young inner bulla (growing) were compared with young otic capsule and 358 genes were identified when adult inner bulla (quiescent) were compared with adult otic capsule. Fourteen genes were involved in bone metabolism of which four genes have been previously discussed in the literature of perilabyrinthine bone biology. Conclusion The gene expression of the otic capsule was significantly different from that of the middle ear. This study identified a number of differentially expressed bone-related mRNAs of potential significance and confirmed the OPG/receptor activator of nuclear factor kappa-B (RANK)/RANK ligand (RANKL) pathway as the key signaling system for the unique behavior of bone cells within the otic capsule. No differentially expressed up- or downstream messengers in the OPG/RANK/RANKL pathway were found.